Personality Types and Language Learning: A Psycholinguistic Perspective on Modern Islamic Boarding School Students - Azizah, Mir'ah (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2024)
One of the characteristics of modern Islamic boarding schools is that the language usedby the elements of modern Islamic boarding schools mostly uses Arabic and English asan effort to answer the challenges of the times so that students become individual learnerswho are also able to guide the community by using various languages effectively andappropriately. Each student has a personality type, either introvert or extrovert, whichcan support or even hinder the success of learning. The ability of modern Islamic boardingschools and students to recognize and use personality types in learning is a reference foreach element to continue to innovate sustainability related to the right methods andapproaches according to the personality type of students in modern Islamic boardingschools.Keywords: Personality, Learners, Language Learning Strategies